Utilizing FeCrAl Oxidation Resistance Properties in Water, Air and Steam for Accident Tolerant Fuel Cladding. (5th April 2018) - Gupta, Vipul K.; Larsen, Michael; Rebak, Raul B.
Abstract : A recent interest in Accident Tolerant Fuel (ATF) cladding for light water reactors has revitalized the attention to iron-chromium-aluminum (FeCrAl) ferritic alloys, which have been used for other purposes for more than eight decades. The main motivation for use of FeCrAl alloys as ATF cladding is that FeCrAl alloys is that FeCrAl alloys are many orders of magnitude more resistant to attack in air and super-heated steam (e.g. >1200°C) than zirconium alloys. Recent research has shown that FeCrAl is also resistant to general corrosion in normal operation conditions (~300°C) hydrogenated water since it develops a continuous protective chromium rich oxide film on its surface. Under accident conditions, in superheated steam, the FeCrAl becomes protected by alumina. If an alumina protected tube is then flooded with fresh water during a quenching operation after the accident, the surface oxide returns to chromia. FeCrAl seems ideal for nuclear applications due to its adaptability to the environment, normal operation or loss of coolant accident.